OC-075 Analysis of Long-Term outcomes after Endoscopic Radiofrequency Ablation for Bile Duct Strictures in Pancreatic Malignancy Suggests Potential Survival Benefit. (4th June 2013) - Kallis, Y; Phillips, N; Steel, A; Kaltsidis, H; Nicholls, J; Jiao, L; Vlavianos, P; Habib, N; Westaby, D
Abstract : Introduction: Pancreatic carcinoma carries a poor prognosis with only 10–20% of patients amenable to attempts at curative surgery at presentation. Biliary obstruction is a common complication and many patients will require self-expanding metal stent (SEMS) insertion for definitive decompression. A recent pioneering phase I/II study in our tertiary referral centre demonstrated excellent safety and 90d stent patency with endobiliary radiofrequency ablation (RFA) as an adjunct to SEMS insertion. The longer-term impact of this novel endoscopic treatment modality on biliary drainage and patient survival in advanced pancreatic carcinoma is unknown. Objective: To investigate the longer-term efficacy of endobiliary RFA in the management of malignant bile duct obstruction associated with inoperable pancreatic carcinoma. Methods: Retrospective cohort analysis of 23 patients with unresectable pancreatic carcinoma undergoing RFA + SEMS insertion, and 46 matched controls undergoing SEMS insertion alone, for malignant biliary obstruction in a single tertiary referral centre. Patients were stringently matched for age, sex, metastases, ASA/co-morbidities, and intention to treat with palliative chemotherapy. Survival, maintenance of stent patency, and procedure-related complications were assessed. Results: RFA and control groups were closely matched- age 68.9 +/- 9.0y vs. 69.8 +/- 9.9y, p = 0.791; ASA 2.35 +/- 0.65 vs. 2.54 +/- 0.50, p = 0.086; metastases at treatment 9/23 (39.1%) vs. 18/46 (39.1%), p = 0.800; chemotherapy 16/23 (69.6%) vs. 24/46 (52.2%), p = 0.203. Median survival was 227d after RFA vs. 123.5d in controls (HR 0.633 CI 0.378–1.060, p = 0.011). RFA was independently predictive of survival at 90d (OR 16.14, CI 1.35–193.18, p = 0.028) and 180d (OR 4.25, CI 1.00–18.01, p = 0.049). Overall SEMS patency rates were the same across both groups, though more patients were alive with a patent index SEMS after RFA within the first few months (73.9% vs. 41.3% at 4.5 m, p = 0.012). Complications of RFA were few (1 pancreatitis, 1 cholangitis), with a median post-procedure inpatient stay of 1d (1–8). Conclusion: In the single largest case series to date, endobiliary RFA was found to be a safe and efficacious adjunctive treatment in the management of patients with advanced pancreatic malignancy and biliary obstruction, and demonstrated potential early survival benefit. These data suggest that endobiliary RFA could be an additional treatment option in advanced pancreatic carcinoma, and form the basis from which future prospective clinical trials of this novel treatment modality can be designed. Disclosure of Interest: Y. Kallis: None Declared, N. Phillips: None Declared, A. Steel: None Declared, H. Kaltsidis: None Declared, J. Nicholls Shareholder of: EMcision Ltd UK, L. Jiao: None Declared, P. Vlavianos: None Declared, N. Habib Shareholder of: EMcision Ltd UK, D. Westaby: None Declared.